Implementasi Metode Bernyanyi dalam Pembelajaran MufradÄt - Ahmad Qomaruddin (Jurnal Kependidikan, 2017)
Language is a system of sound symbol used by a particular group of people to communicate and interact. The success of language learning is influenced by the learning method, which facilitate the ease of learning. One aspect of Arabic language learning is mufradÄt. MufradÄt is a means or medium for learning Arabic, not the goal of learning Arabic. However, there is no doubt that vocabulary (mufradÄt) is important in the learning a foreign language, not the exception, Arabic. The application of the singing method, i.e. introducing a new song to students and facilitating them to sing the song completely and verse to verse, is expected to be able to increase reference and improve the quality of learning Arabic, especially in learning mufradÄt.